2010
DOI: 10.1007/s10393-010-0634-1
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquity of the Pathogenic Chytrid Fungus, Batrachochytrium dendrobatidis, in Anuran Communities in Panamá

Abstract: The pathogenic chytrid fungus, Batrachochytrium dendrobatidis, has been implicated as the main driver of many enigmatic amphibian declines in neotropical sites at high elevation. Batrachochytrium dendrobatidis is thought to be a waterborne pathogen limited by temperature, and the extent to which it persists and causes disease in amphibians at lower elevations in the neotropics is not known. It also is unclear by what mechanism(s) B. dendrobatidis has emerged as a pathogenic organism. To test whether B. dendrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 56 publications
6
39
1
1
Order By: Relevance
“…We have shown that, in Panama, lizards and snakes will harbour B. dendrobatidis DNA at non-pathological levels of prevalence and intensity that are comparable to those found among anuran amphibians that are not showing signs of chytriomycosis disease (Kilburn et al 2011). Without histology, we cannot say that we have proven the presence of B. dendrobatidis infection or the presence of infective zoospores on the reptiles, but the assays we used are routinely considered diagnostic for B. dendrobatidis infection in amphibians and, therefore, our findings indicate that infection is highly plausible.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…We have shown that, in Panama, lizards and snakes will harbour B. dendrobatidis DNA at non-pathological levels of prevalence and intensity that are comparable to those found among anuran amphibians that are not showing signs of chytriomycosis disease (Kilburn et al 2011). Without histology, we cannot say that we have proven the presence of B. dendrobatidis infection or the presence of infective zoospores on the reptiles, but the assays we used are routinely considered diagnostic for B. dendrobatidis infection in amphibians and, therefore, our findings indicate that infection is highly plausible.…”
Section: Discussionmentioning
confidence: 95%
“…No individual reptile that tested positive for Batrachochytrium dendrobatidis DNA showed either the symptoms of chytridiomycosis disease or the elevated levels of infection intensity notable in anuran amphibians stricken with chytridiomycosis (Kilburn et al 2011).…”
Section: Intensity Of Batrachochytrium Dendrobatidis Dna On Reptilesmentioning
confidence: 99%
See 3 more Smart Citations